2021
DOI: 10.1371/journal.pone.0249757
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of late embryogenesis abundant protein-encoding genes in rye (Secale cereale L.)

Abstract: Late embryogenesis abundant (LEA) proteins are members of a large and highly diverse family that play critical roles in protecting cells from abiotic stresses and maintaining plant growth and development. However, the identification and biological function of genes of Secale cereale LEA (ScLEA) have been rarely reported. In this study, we identified 112 ScLEA genes, which can be divided into eight groups and are evenly distributed on all rye chromosomes. Structure analysis revealed that members of the same gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Among the 50 LEA genes that we identified in the sp9512 genome, 13 are upregulated in turions and varied from 11- to over 2,000-fold. Interestingly, 5 out of the top 6 highly expressed LEA genes in turions are most homologous in sequence to seed-specific LEAs in rye (Ding et al ., 2021), suggesting that similar preference for those types of LEAs with distinct functions is shared between seeds and turions (Fig. S8).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 50 LEA genes that we identified in the sp9512 genome, 13 are upregulated in turions and varied from 11- to over 2,000-fold. Interestingly, 5 out of the top 6 highly expressed LEA genes in turions are most homologous in sequence to seed-specific LEAs in rye (Ding et al ., 2021), suggesting that similar preference for those types of LEAs with distinct functions is shared between seeds and turions (Fig. S8).…”
Section: Resultsmentioning
confidence: 99%
“…The differential expression of the VrLEA-55 gene in both treatments could be attributed to mechanical injury in addition to heat stress in the detached leaf method as compared to the in planta method. Ding et al (2021) also noticed the expression of this gene in different tissues, including seeds of rye, in drought stress although the expression was non-significant. Our study reports the expression of this candidate gene in the leaves of the HT-wild Vigna genotype and provides a new insight to heat tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of the wheat DHN-5 was reported to enhance osmotic stress tolerance in Arabidopsis ( Brini et al, 2011 ). Ding et al (2021) reported the maximum expression of LEA genes under polyethylene glycol (PEG) treatment, low temperature, and light intensity deviations in the case of rye. Therefore, the above-mentioned studies demonstrate that the LEA genes could potentially be used to improve the abiotic stress tolerance of crops.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 50 LEA genes that we identified in the sp9512 genome, 13 are upregulated in turions and varied from 11-to over 2000-fold. Interestingly, five out of the top six highly expressed LEA genes in turions are most homologous in sequence to seed-specific LEAs in rye (Ding et al, 2021), suggesting that similar preference for those types of LEAs with distinct functions is shared between seeds and turions (Fig. S8).…”
Section: Comparative Analysis Of Global Transcriptomes Between Mature...mentioning
confidence: 99%